Estimating multidimensional density functions using the Malliavin-Thalmaier formula - Kohatsu Higa, Arturo; Yasuda, Kazuhiro (Pro Mathematica, 2007)
The Malliavin-Thalmaier formula was introduced for simulation of high dimensional probability density functions. But when this integration by parts formula is applied directly in computer simulations, we show that it is unstable. We propose an approximation to the Malliavin-Thalmaier formula. In this paper, we find the order of the bias and the variance of the approximation error. And we obtain an explicit Malliavin-Thalmaier formula for the calculation of Greeks in finance. The weights obtained are free from the curse of dimensionality.